Microwave-assisted tandem catalyst-free production of 2-methyl furoate from furfural - Guerrero, Maira Antonela (2024)
The valorization of building blocks present in vegetal biomass using eco-efficient processes is an excellent alternative to reduce the demand for fossil fuels. Furfural is an encouraging renewable biomass-based platform chemical that can be transformed into several value-added chemicals.The transformation of furfural into methyl furoate through a tandem process that involves oxidation followed by esterification with methanol is widely studied since the selectivity towards the product is strongly dependent on numerous factors: reaction conditions, oxidant, and catalysts.Depending on them, more than ten different products can be obtained, making the process of no importance given the difficulty of separating each of these products. In this communication we study the reaction selectivity in a very simple procedure that is catalyst-free, using a clean oxidant and mild reaction conditions. Particularly as an alternative source of heat, and with the aim of reducing reaction times, said transformation was assisted by microwaves. In order to optimize the process, the reaction time and temperature, type of oxidant, amount of oxidant and molar ratio of reagents were studied. In this work, 100% conversion with 69% selectivity was achieved in 2 h at 120 °C using 1:3:20 M ratio of furfural, oxidant, and alcohol. The methodology represents a powerful alternative for the preparation of furoates through a low-cost and environmentally friendly process that does not use a catalyst.